Mount Sinabung Eruption Collaboration Model in a Disaster Political Perspective - Pasaribu, Ian; Adela, Fernanda Putra (Talenta Publisher, 2019)
This research, explained and analyzed the collaboration model of eruption of Mount Sinabung eruption in a disaster political perspective. Located in Karo District, North Sumatra Province in the last 6 years from 2010-2016 regularly experienced eruptions. There are still countermeasures problems considering there are still obstacles faced by (stakeholders). The formulation of this research is how the cooperation and coordination of stakeholders in the eruption prevention of Mount Sinabung. What is the policy of disaster disasters in North Sumatra that has not succeeded in completing the eruption of Mount Sinabung. The theoretical framework of this study using the concept of cooperation, good governance in disaster management, coordination and disaster management concepts then to analyze researchers has mapped the role of different stakeholders such as the central government, local government, employers, NGOs and the community. This research is a qualitative research with a critical paradigm to explain phenomena and find new models by placing an interview as primary data and books, international journals and national journals. The results of this study indicate that the collaborative model of Sinabung eruption cooperation is coordinating Mount Sinabung stakeholders, eruption disaster management, disaster management policy constraints in North Sumatra that have not succeeded in completing the Sinabung eruption, disaster management policy recommendations for the Mount Sinabung eruption. At the end of the results of this study, the scheme of the model for collaborative disaster management and also explaining the importance of Sinabung became a national disaster